MIB-1 Index as a Surrogate for Mitosis-Karyorrhexis Index in Neuroblastoma. (August 2015) - Atikankul, Taywin; Atikankul, Yupapin; Santisukwongchote, Sakun; Marrano, Paula; Shuangshoti, Shanop; Thorner, Paul S.
<x xml:space="preserve">Abstract</x> Neuroblastoma, the most common extracranial solid tumor in infancy, shows marked biological heterogeneity. Multiple prognostic markers are combined to risk-stratify neuroblastoma patients for treatment. One marker assesses histology, dividing patients into favorable and unfavorable categories based, in part, on the mitosis-karyorrhexis index (MKI). The recommended scoring of 5000 cells is, however, time-consuming and observer-dependent, and accurate counts may not always be performed. In the present study, we investigated using MIB-1 as a surrogate marker for the MKI. Twenty-five cases of neuroblastoma, ranging from low to high MKI, were immunostained for MIB-1. A total of 375 microscopic fields were digitally captured with >100, 000 cells scored. The MIB-1 index was determined by image analysis and MKI, by manual counting of the same immunostained fields. There was a significant correlation between the MIB-1 index and MKI comparing all fields (r=0.7869, P<0.01) and an even better correlation comparing individual cases (r=0.9147, P<0.01). Using a linear regression model, a formula was generated to calculate MKI from the MIB-1 index as follows: MKI=(MIB-1 index×0.124)+1.412. With this formula, a low MKI corresponds to an MIB-1 index <4.74, intermediate MKI to an MIB-1 index of 4.74 to 20.87, and high MKI to an MIB-1 index >20.87. For comparison, the calculations were repeated using a manual MIB-1 count on the same images. Similar significant correlations were obtained, with nearly identical cutoff values for MKI categories. This approach can facilitate determination of the MKI by assessing the MIB-1 index, either by image analysis or manual counting.